PERTANGGUNGJAWABAN PIDANA PERUSAHAAN PEMBIAYAAN YANG MELAKUKAN EKSEKUSI OBJEK JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR : 18/PUU-XVII/2019 - Puguh Ari Wijayanto (2021)
After the decision of the Constitutional Court Number : 18/PUU-XVII/2019, financing company which carrying out the execution of fiduciary guarantee objects have to meet two conditions, i.e. the agreement between assignor and assignee of fiduciary related to the default in financial agreement and the willingness of the debtor to submit their fiduciary guarantee objects. Therefore, the execution can only be carried out through and valid with court judgement execution implementation which has permanent legal force, as of the financing companies which keep to carry out the execution of fiduciary guarantee objects will be caused legal issues, especially criminal law. The regulation of Financial Service Authority number 35/POJK.05/2018 about Financing Company Services Implementation, give some options for financing company to carry out independent execution or involve the third party. The financing company which keep to carry out the execution after Constitution Court decision, the employee have to be fully responsible regarding the criminal issues and may be subjected to article 368 Paragraph (1) of the Criminal Code. While the execution which involving the third party is third party responsibility if they violate one of the conditions of Constitution Court decision. Thus, it is necessary to revise the Law No. 42 of 1999 about Fiduciary Guarantees on the implementation of fiduciary guarantees after Constitutional Court decision number 18/PUU-XVII/2019.